Rain fade duration prediction models for a high elevation angle based on measured data in tropical climate - Dao, Hassan; Zuhairi, Megat Farez Azril; Islam, Md Rafiqul (Elsevier Ltd, 2018)
Rain fade duration is one of the essential components for engineers to design and plan satellite communication systems at high frequency bands. In this paper, rain fade duration was obtained for twelve consecutive months at Ku-band with 77.4 elevation angle from MEASAT3 in Kuala Lumpur, Malaysia. Empirically, the fade duration was found discrepant to the results predicted by models. Therefore, a modification of fade duration model is proposed based on measured data for this tropical climate and high elevation angle.